Resposta :
Resposta:
d
Explicação passo-a-passo:
(3²+2×3×(√2)²)-1=
= (9+6√2+2)-1=
=11+6√2-1=
=10+6√2
Resposta:
d)
Explicação passo-a-passo:
Para resolver você usa produtos notáveis a saber:
[tex] {(a + b)}^{2} = {a}^{2} + 2 \times a \times b + {b}^{2} [/tex]
Logo
[tex]{a}^{2} = {(3 + \sqrt{2})}^{2} \\ {a}^{2} = {3}^{2} + 2 \times 3 \times \sqrt{2} + {( \sqrt{2} )}^{2} \\ {a}^{2} = 9 + 6 \sqrt{2} + 2 \\ {a}^{2} = 11 + 6 \sqrt{2 } \\ \\ {a}^{2} - 1 = 11 + 6 \sqrt{2} - 1 \\ {a}^{2} - 1 = 10 + 6 \sqrt{2} [/tex]